Muscle Satellite Cell Heterogeneity: Does Embryonic Origin Matter? - Rodriguez-Outeiriño, Lara; Hernandez-Torres, Francisco; Ramírez-de Acuña, F.; Matías-Valiente, Lidia; Sanchez-Fernandez, Cristina; Franco, Diego; Aranega, Amelia Eva (Frontiers in Cell and Developmental Biology, 2021)
Muscle regeneration is an important homeostatic process of adult skeletal muscle that recapitulates many aspects of embryonic myogenesis. Satellite cells (SCs) are the main muscle stem cells responsible for skeletal muscle regeneration. SCs reside between the myofiber basal lamina and the sarcolemma of the muscle fiber in a quiescent state. However, in response to physiological stimuli or muscle trauma, activated SCs transiently re-enter the cell cycle to proliferate and subsequently exit the cell cycle to differentiate or self-renew. Recent evidence has stated that SCs display functional heterogeneity linked to regenerative capability with an undifferentiated subgroup that is more prone to self-renewal, as well as committed progenitor cells ready for myogenic differentiation. Several lineage tracing studies suggest that such SC heterogeneity could be associated with different embryonic origins. Although it has been established that SCs are derived from the central dermomyotome, how a small subpopulation of the SCs progeny maintain their stem cell identity while most progress through the myogenic program to construct myofibers is not well understood. In this review, we synthesize the works supporting the different developmental origins of SCs as the genesis of their functional heterogeneity.